Difficulties and Correlation between Phenomenon and Reasoning Tier of Multiple-Choice Questions: A Survey Study - HILMAN QUDRATUDDARSI; RENUKA V SATHASIVAM; HUTKEMRI HUTKEMRI (Universitas Jambi, 2019)
Two-tier multiple-choice (2TMC) has been introduced as an instrument to analyze a conceptual understanding at tier 1 and reasoning to the answer at tier 2. Even there are many studies on using the instrument; there is still relatively little attention on scoring method. Therefore, this study aimed to compare difficulties and to see if there is a correlation between responses at the phenomenon and reasoning tier. The instrument namely representational systems and chemical reaction diagnostic instrument (RSCRDI) containing 15 items were translated into Indonesian language and validity and reliability of the instrument were established. RSCRDI was tested with 185 pre-service chemistry teachers (19 males and 166 females). Their raw data were converted into logit, and it was found that the phenomenon tier was slightly more difficult. Based on Pearson correlation test, it is found that the phenomenon tier and reasoning tier were significantly correlated, r=.362, p-value <0.001.